Rejuvenescence American Style: Longevity, Aging, The US Tradition of Rejecting the Old & the US Baby Boom Generation Now - John Dean (Transatlantica)
This Cultural History essay’s focus is age, aging, longevity and the consciousness of a generation in contemporary United States and the verifiable foundations of these issues: how age is real and artificial both. Frames that define understanding of age are physical, of course, but frames are also created and imposed by a civilization. This essay seeks to analyze what aging means for the US Baby Boomer generation, a group which, as no other in the nation’s history, defined itself as young. To accomplish this investigation the essay tries to blend Cultural History, Cohort Analysis, Sociology of Mass Media, American Studies, and Cross-cultural analysis. Key American civilization traits are used as analytical tools: The Promised Land, Progress, Superabundance, Innocence, Rejuvenation, Success, Opportunity, Ingenuity, Technology, Declaration of Independence, The Constitution, The Founding Fathers, Isolationism